Identifikasi Molekular Kekerabatan Genetik Kopi Wamena Berbasis Marka Random Amplified of Polymorphic DNA (RAPD) - I Made Budi; Arsyam Mawardi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2021)
Baliem Coffee or Wamena Arabica Coffee is classified as a specialty coffee that has a distinctive aroma and taste as one of the world's best coffees. Wamena coffee has a high commercial value, there are many advantages of Wamena coffee. Growing on a variety of soil types, elevation, coffee variety, and durable. The quality of Wamena coffee must be maintained by the local government. However, this elite coffee germplasm is threatened with extinction and is in a dangerous situation due to habitat destruction due to forest clearing, land use change and the potential for competition with various disease-resistant varieties. This study aims to identify molecularly the genetic relationship of Wamena Arabica coffee in Jayawijaya district with the Random Amplified Polymorphic DNA (RAPD) markers as molecular markers. The stages in this study were sample collection, morphological observations, genomic DNA extracted using the CTAB method, gene amplification process using PCR-RAPD molecular markers with ten primers, measurement of DNA concentration using a spectrophotometer, and data analysis using UPGMA NTSYS version 2.1. The electroferogram results showed that pRAPD1, pRAPD2 and pRAPD5 primers produced a band pattern with high polymorphism as well as indicating the genetic diversity of the Coffea arabica L. arabica coffee samples tested. Based on the dendogram construction analysis, the arabica coffee sample Coffea arabica L. which was tested on 5 coffee genotypes, obtained 2 coffee groups, namely Group 1 consisting of one variety, namely sample (V) Arabica Typica from the Assolokobal area. Group 2 with four varieties, namely samples (I) Arabica Catimor, (II) USDA, (III) Arabica PM 88, and (IV) Arabica Linies 795, from Wollo. Phylogenetic tree construction resulted in a similarity coefficient of 83%, indicating the high relationship between Arabica coffee populations. The results of this study have obtained a genetic fingerprint profile of wamena specialty arabica coffee, namely its genetic relationship. The superiority of the genetic composition of Wamena coffee in Jayawijaya district in the future has the potential to be derived through much more advanced molecular technology.